Advanced aortic imaging and intervention - Zucker, Evan J.; Prabhakar, Anand M.; Ganguli, Suvranu (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2018)
This special issue of Cardiovascular Diagnosis and Therapy focuses on updates in advanced aortic imaging and intervention. Aortic diseases are a leading cause of morbidity and mortality worldwide, only likely to increase in incidence with an everaging population.